Effectiveness of RLTH Development in Madiun District - Wuryani, Siti (Decision, 2024)
A house, as a place of residence, is one of the essential needs for human life alongside clothing and food. It plays a crucial role in ensuring the well-being, safety, and quality of life of individuals. More than just shelter, a house serves as a strategic center for family activities, particularly in educating and nurturing family members. However, not all families are able to afford decent housing due to various challenges, especially economic limitations. To address this issue, the local government of Madiun Regency has implemented a housing rehabilitation assistance program for low-income households (MBR) that meet specific criteria, such as legal land ownership, unsuitable current housing conditions, and no previous aid received. The selection of recipients is based on the Integrated Social Welfare Data (DTKS) or recommendations from village heads forwarded to the Housing and Settlement Area Office. From 2018 to 2021, the program effectively improved 9,010 uninhabitable homes (RTLH), and it is expected to continue efficiently in the coming years.